Interference with Ubiquitination in CFTR Modifies Stability of Core Glycosylated and Cell Surface Pools - Lee, Seakwoo (American Society for Microbiology, 2014)
It is recognized that both wild-type and mutant CFTR proteins undergo ubiquitination at multiple lysines in the proteins and in one or more subcellular locations. We hypothesized that ubiquitin is added to specific sites in wild-type CFTR to stabilize it and at other sites to signal for proteolysis. Mass spectrometric analysis of wild-type CFTR identified ubiquitinated lysines 68, 710, 716, 1041, and 1080. We demonstrate that the ubiquitinated K710, K716, and K1041 residues stabilize wild-type CFTR, protecting it from proteolysis. The polyubiquitin linkage is predominantly K63. N-tail mutants, K14R and K68R, lead to increased mature band C CFTR, which can be augmented by proteasomal (but not lysosomal) inhibition, allowing trafficking to the surface. The amount of CFTR in the K1041R mutant was drastically reduced and consisted of bands A/B, suggesting that the site in transmembrane 10 (TM10) was critical to further processing beyond the proteasome. The K1218R mutant increases total and cell surface CFTR, which is further accumulated by proteasomal and lysosomal inhibition. Thus, ubiquitination at residue 1218 may destabilize wild-type CFTR in both the endoplasmic reticulum (ER) and recycling pools. Small molecules targeting the region of residue 1218 to block ubiquitination or to preserving structure at residues 710 to 716 might be protein sparing for some forms of cystic fibrosis.